Line intensities and self-broadening coefficients of CH3I in the region of ν5 and ν3+ν6 bands. (November 2021) - Fathallah, O. Ben; Hmida, F.; Boughdiri, A.; Manceron, L.; Rotger, M.; Aroui, H.
Abstract: Systematic measurements of self-broadening coefficients for 992 transitions in the ν5 and ν3 +ν6 perpendicular bands of CH3 I up to the quantum numbers 3 ≤ J ≤ 52 and 0 ≤ K ≤ 12 have been performed for the first time using a mono-spectrum fitting technique utilizing a Voigt profile. Our previous line intensity measurements [Boughdiri, et al., JQSRT 221 (2018) 147-154] are also extended using new spectra recorded at room temperature at five pressures from 1.15 to 9.98 mbar using the Bruker IFS125HR Fourier Transform spectrometer at the AILES beamline of the SOLEIL Synchrotron facility. The measured absolute intensities were used to derive the transition dipole moment squared for each line, the band intensities as well as the Herman–Wallis coefficients. The rotational dependences of the self-broadening coefficients have been clearly observed and modeled. The data were compared with previous works. The results are given as supplementary data table for a possible use in atmospheric and industrial applications. Highlights: Line-by-line measurements of line intensities in the ν5 and ν3 +ν6 bands of CH3 I were performed. Transition dipole moments squared were derived for about 1150 lines. Analysis of the line intensities and transition dipole moments squared was performed. The intensity parameters were retrieved. Self-broadening coefficients have been measured and modeled.